2011
DOI: 10.1111/j.1469-7998.2011.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Ancient hybridization and underestimated species diversity in Asian striped squirrels (genus Tamiops ): inference from paternal, maternal and biparental markers

Abstract: Current classification of the genus Tamiops is mainly based on pelage color pattern that is prone to seasonal variation or convergent adaptation to environmental selection. The arrangement of four species, Tamiops mcclellandii, Tamiops rodolphii, Tamiops swinhoei and Tamiops maritimus, is regarded as tentative due to difficulty in delineating species, especially the latter two species. We constructed multi-locus phylogenies of all four Tamiops species on the basis of paternal (Y-chromosomal SRY and SMCY7), mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 34 publications
1
8
1
Order By: Relevance
“…Subsequently during the interglacial period, rising sea levels isolated Hainan Island and triggered the genetic divergence between L HN and L S . Different from the phylogenetic trees based on mitochondrial genes, the trees of nuclear genes showed that our specimens from the 2 sampling sites, Longzhou (Site 6) and Yongshun (Sites 10), formed a monophyletic group (L W ), inferring the ancient hybridization between lineages L N and L S in these regions (Chang et al 2011). These 2 sampling sites are approximately 500 m in elevation, located in the transient zone between the second and third topography steps of China (Fig.…”
Section: Evolutionary History Of the Leopoldamys Edwardsi Complexcontrasting
confidence: 73%
“…Subsequently during the interglacial period, rising sea levels isolated Hainan Island and triggered the genetic divergence between L HN and L S . Different from the phylogenetic trees based on mitochondrial genes, the trees of nuclear genes showed that our specimens from the 2 sampling sites, Longzhou (Site 6) and Yongshun (Sites 10), formed a monophyletic group (L W ), inferring the ancient hybridization between lineages L N and L S in these regions (Chang et al 2011). These 2 sampling sites are approximately 500 m in elevation, located in the transient zone between the second and third topography steps of China (Fig.…”
Section: Evolutionary History Of the Leopoldamys Edwardsi Complexcontrasting
confidence: 73%
“…Two M. avellanarius species would be recognized under the GSC (Baker and Bradley 2006). The cytb divergence between Lineage 1 and Lineage 2 is high (10.3 %) and comparable to that found between Asian striped squirrels (genus Tamiops; T. maritimus and T. swinhoei) (Chang et al 2011) or between dormice species (genus Eliomys; E. quercinus and E. melanurus) (Montgelard et al 2003). However, recent studies have also revealed that ''intraspecific'' divergences in species from monotypical genera can be also very deep (e.g.…”
Section: Species Delimitationsupporting
confidence: 70%
“…Regional variation in C. finlaysonii is so extreme that it is doubtful that all these forms constitute discrete species (Corbet & Hill 1992), while hybrids may occur in certain regions where both species occur (Moore & Tate 1965;Timmins & Duckworth 2008). Genetic introgression between subspecies, and even between species, has been reported in other squirrels given the hybridization that frequently occurs in pet markets and stores (Wettstein et al 1995;Good et al 2008;Hird & Sullivan 2009;Chang et al 2011). Oshida et al (2007) and Kuramoto et al (2012) concluded that the squirrels introduced into Japan that had been identified as C. erythraeus but were genetically closer to C. finlaysonii could be regarded either as C. finlaysonii or as hybrids between both species.…”
Section: Discussionmentioning
confidence: 99%